Estudio de factibilidad para la creación de una empresa de Patacones Pre cocidos y Congelados en la Ciudad de Cali -Valle (2016)
The purpose of this project is to determine the feasibility in terms of market, economic investment, technical and operational capacity and infrastructure, as well as the influence, participation, acceptance and environmental impact that can generate the creation of a company that is responsible for the production and marketing of pre-cooked plantains in the city of Cali. In the initial stage of this project a diagnosis on the market for precooked and frozen products, especially products made from bananas, culture and consumption trends in the city of Cali, performance and participation in this sector and its share is presented in the economy of Cali and Valle del Cauca. For this information to primary sources of direct communication (interviews and observation) and secondary sources as DANE statistics, Thesis concerning this subject, information from the Chamber of Commerce of Cali, FENALCO and Databases was used University of Quindío. The results obtained through these media, will determine the knowledge of consumer culture, tastes, behavior, shopping trends, characteristics of preparation, frequency and acceptance that may have pre-cooked plantains in the city of Cali, and possible entry and participation in this market.